Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages calculated to free the individual from physical want during periods of unemployment and sickness. The scales of benefit are 24/- for a single person and 40/- for a man and wife, with children's allowances in addition. The reason for so fixing benefits is closely argued in the Report so that one can see at a glance the justification for fixing benefits at this level and no other. This is a big advantage. The Government is forced to defend a given rate of benefits on the basis of a given subsistence level. At present the National Health Insurance Benefit is fixed at a level corresponding to the financial position of the various approved societies but far below even the lowest subsistence scale that could be imagined. But with the operation of the Beveridge scheme benefits will be related to a clearly defined scale of subsistence whose adequacy can be examined. The benefits of 24/- and 40/- assume a cost of living level 25% above that of 1938, and are supposed to be spent as follows on the basis of assumed prices:— Food (Man and Wife), 16/3; Clothing, 3/9; Fuel, Light and Sundries, 5/-; Rent, 12/6. This leaves a margin of 2/6 for inefficiency in purchasing, and for the fact that "people in receipt of the minimum income required for subsistence, will, in fact, spend some of it on things not absolutely necessary." It will be noted that the subsistence level provides for food, clothing, and shelter, and next to nothing else. Yet the Ministry of Labour Enquiry into the expenditure of working-class households in 1938 revealed that 30% of the expenditure in urban households was for items other than food, clothing, rent, lighting and fuel. In the households of agricultural workers and in other working-class households in rural areas the proportion of total expenditure on these other items was 24%. 10 15X/2/103/272